Cognitive Radio Optimal Path for Dynamic Spectrum Access - Murthy, H.Srinivasa; Kumar, S.Phani (2024 International Conference on Knowledge Engineering and Communication Systems (ICKECS), 2024)
Cognitive Radio (CR) technology has gained prominence for its ability to facilitate dynamic spectrum access (DSA), enabling opportunistic access to underutilized frequency bands. In the context of DSA, efficient path selection is crucial for optimizing spectrum utilization and mitigating interference. This paper presents a novel approach that combines Cognitive Radio along nets of ant to address the challenge of finding the optimal path for dynamic spectrum access in wireless communication networks. The intelligence of Ant nets/ant colony optimization algorithms to navigate the dynamic spectrum landscape effectively. By deploying a swarm of virtual agents that emulate the foraging behavior of ants, CR [4,5] devices can collaboratively discover and select the most suitable paths for spectrum access. These paths are evaluated based on multiple criteria, including spectrum availability, interference levels, Quality of Service (QoS) requirements, and network topology.ACO (Ant colony optimization) algorithm's pheromone-based approach allows CR devices to adapt and learn from their experiences, thus improving decision-making over time. This adaptability is crucial in dynamic environments where spectrum conditions can change rapidly The ACO-CR approach enhances the ability of CR devices to find and utilize the most appropriate path, avoiding congested or interference-prone channels.Simulation results demonstrate the efficacy of the ACO-CR algorithm in optimizing dynamic spectrum access. [14, 15]It outperforms conventional static path selection methods and exhibits superior adaptability to changing network conditions. The collaborative nature of ACO-CR enables more efficient spectrum utilization, reduced interference, and better QoS fulfillment for diverse applications.to address the critical issue of optimal path selection for dynamic spectrum access. The synergy between CR and ACO offers a promising solution for improving spectrum utilization, network performance, and the quality of wireless communication services in a dynamic and ever-changing radio frequency Environment.